2002
DOI: 10.1104/pp.010835
|View full text |Cite
|
Sign up to set email alerts
|

Phosphite, an Analog of Phosphate, Suppresses the Coordinated Expression of Genes under Phosphate Starvation

Abstract: Phosphate (Pi) and its analog phosphite (Phi) are acquired by plants via Pi transporters. Although the uptake and mobility of Phi and Pi are similar, there is no evidence suggesting that plants can utilize Phi as a sole source of phosphorus. Phi is also known to interfere with many of the Pi starvation responses in plants and yeast (Saccharomyces cerevisiae). In this study, effects of Phi on plant growth and coordinated expression of genes induced by Pi starvation were analyzed. Phi suppressed many of the Pi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
142
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(153 citation statements)
references
References 38 publications
3
142
1
7
Order By: Relevance
“…Os resultados do primeiro experimento demonstraram claramente que o fosfito não substituiu o fosfato na nutrição fosfatada do feijoeiro, fato observado em outros trabalhos com outras culturas, tanto em solo (Lucas et al, 1979;Schröetter et al, 2006) quanto em solução nutritiva (Carswell et al, 1996;Föster et al, 1998;Ticconi et al, 2001;Varadarajan et al, 2002;Singh et al, 2003;Ávila et al, 2011). Destacou-se a alta sensibilidade do feijoeiro ao fosfito na ausência de fosfato, tendo em vista a rápida manifestação de toxicidade e a paralisação de seu crescimento, sob a concentração maior que 0,5 mg L -1 de P-Phi.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Os resultados do primeiro experimento demonstraram claramente que o fosfito não substituiu o fosfato na nutrição fosfatada do feijoeiro, fato observado em outros trabalhos com outras culturas, tanto em solo (Lucas et al, 1979;Schröetter et al, 2006) quanto em solução nutritiva (Carswell et al, 1996;Föster et al, 1998;Ticconi et al, 2001;Varadarajan et al, 2002;Singh et al, 2003;Ávila et al, 2011). Destacou-se a alta sensibilidade do feijoeiro ao fosfito na ausência de fosfato, tendo em vista a rápida manifestação de toxicidade e a paralisação de seu crescimento, sob a concentração maior que 0,5 mg L -1 de P-Phi.…”
Section: Discussionunclassified
“…Destacou-se a alta sensibilidade do feijoeiro ao fosfito na ausência de fosfato, tendo em vista a rápida manifestação de toxicidade e a paralisação de seu crescimento, sob a concentração maior que 0,5 mg L -1 de P-Phi. Em outras espécies vegetais, esse efeito foi observado apenas em concentrações entre 2,0 e 30 mg L -1 de P-Phi (Föster et al, 1998;Ticconi et al, 2001;Varadarajan et al, 2002;Singh et al, 2003). Os mecanismos fisiológicos e, ou, bioquímicos da toxicidade por fosfitos são pouco compreendidos em vegetais.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…. The literature shows that some previous studies also found harmful effects of phosphite anion on plants grown under low phosphate availability, but no harmful effects have been reported when this anion was applied in plants grown under adequate phosphate availability (TICCONO et al, 2001;VARADARAJAN et al, 2002;LEE et al, 2005;SCHROETTER et al, 2006;DEVAIAH et al, 2007;THAO et al, 2008;MOOR et al, 2009;ÁVILA et al, 2011). However, most of these studies were based in Arabidopsis, vegetables, seedlings, citrus, and some cereals, but there is still little information on the effects of phosphite on leguminous plants, especially on grain yield of leguminous.…”
Section: Resultsmentioning
confidence: 99%
“…The causes of this effect are not well understood. There is the hypothesis that plants did not metabolize phosphite anion, and this anion may suppress some plant responses to phosphate deficiency, such as synthesis of phosphatases and P transporters (TICCONI et al, 2001;VARADARAJAN et al, 2002;ÁVILA et al, 2011).…”
Section: Resultsmentioning
confidence: 99%